Pengaruh Kepemimpinan Efektif, Lingkungan Kerja Dan Kompetensi Terhadap Kinerja Pegawai - Iin Herlena H; Baihaqi; Yumiati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
This study aims to prove empirically the effect of effective leadership, work environment, and competence on the performance of echelon IV officials in North Bengkulu Regency. This type of quantitative research uses a survey method. The population was all Echelon IV officials in the Regional Government of North Bengkulu Regency, totaling 659 echelon IV officials and a sample of 249 people. Data were processed using the SPSS program with multiple linear regression. The data collection technique used a questionnaire. The data analysis method consisted of data quality test, classical assumption test, and hypothesis testing. Research results: effective leadership, work environment, and competence have a positive and significant effect on the performance of echelon IV employees in North Bengkulu Regency. Changes in the performance of echelon IV employees in North Bengkulu Regency are determined by effective leadership, work environment, and competence by 41.6%. Suggestion: in carrying out the main duties and functions of each regional work units, echelon IV officials are expected to apply effective leadership behavior that is relationship-oriented or change-oriented, to create a comfortable work environment in support of employee performance improvement, regional work units should propose and budget for improvement. the quality of work facilities and infrastructure through programs and activities in each regional work units, to improve the performance of echelon IV officials in North Bengkulu Regency, it is hoped that the Regional Government will provide opportunities for echelon IV officials to increase their competence through leadership education and training, and provide support The budget for Education and Training activities and other technical training, as well as through related agencies (BKPSDM) in placing employees in echelon IV positions must be in accordance with the competence of their duties and jobs (the right man and the right job).